Boundary layers in turbulent vertical convection at high Prandtl number. (10th January 2022) - Howland, Christopher J.; Ng, Chong Shen; Verzicco, Roberto; Lohse, Detlef
Abstract: Abstract : Many environmental flows arise due to natural convection at a vertical surface, from flows in buildings to dissolving ice faces at marine-terminating glaciers. We use three-dimensional direct numerical simulations of a vertical channel with differentially heated walls to investigate such convective, turbulent boundary layers. Through the implementation of a multiple-resolution technique, we are able to perform simulations at a wide range of Prandtl numbers ${Pr}$ . This allows us to distinguish the parameter dependences of the horizontal heat flux and the boundary layer widths in terms of the Rayleigh number $\mbox {Ra}$ and Prandtl number ${Pr}$ . For the considered parameter range $1≤ Pr ≤ 100$, $10^{6} ≤ \mbox {Ra} ≤ 10^{9}$, we find the flow to be consistent with a 'buoyancy-controlled' regime where the heat flux is independent of the wall separation. For given ${Pr}$, the heat flux is found to scale linearly with the friction velocity $V_*$ . Finally, we discuss the implications of our results for the parameterisation of heat and salt fluxes at vertical ice–ocean interfaces.